ANALYSIS OF THE DEVELOPMENT OF SMALL BUSINESS AND ENTREPRENEURSHIP IN SURKHANDARYA REGION (European Journal of Interdisciplinary Research and Development, 2025)
This study provides a comprehensive analysis of the development status, structural changes, and the role of small businesses and entrepreneurship entities in the regional economy of Surkhandarya region. The research evaluates the dynamics in the number of small business entities and assesses their contribution to gross regional product, employment, and investment formation based on statistical data. In addition, the effectiveness of state support mechanisms aimed at promoting small business development, access to financial resources, and infrastructural conditions is analyzed.